Feeding habits of extant and fossil canids as determined by their skull geometry. (11th December 2014) - Meloro, C.; Hudson, A.; Rook, L.
Abstract The canids belong to one of the most prominent families of mammalian carnivores. Feeding adaptations of extant species is well documented by field observations; however, we are still missing palaeoecological insights for many enigmatic fossil specimens. We employ geometric morphometrics to quantify skull size and shape in extant and fossil members of the Canini tribe, inclusive of jackals and wolf‐like taxa. Skull data are tested to identify correlates of dietary adaptations in extant species for predicting adaptations in fossils. Main vectors of shape variation correlate with the relative skull‐palatal length, the position of the upper carnassial tooth and the anterior tip of the secondary palate. Allometry occurs in the palatal shape but size explains only a small fraction (about 4%) of shape variance. Although we quantified only palatal and tooth shape for the inclusion of fragmentary fossils, discriminant function analysis successfully classify extant Canini in dietary groups (small, medium and large prey specialist) with 89% of accuracy. The discriminant functions provide insights into many enigmatic specimens such as Eucyon adoxus (=small prey), fossil jackal‐like from Koobi Fora formation (=small prey) and the Plio‐Pleistocene Old World canid guild (Canis etruscus, C. arnensis and Lycaon falconeri). Clearly, both skull size and shape are excellent predictors of feeding habits in Canini thus also provide information about fossil taxonomic affinities.